PENINGKATAN MUTU PENDIDIKAN TINGGI MELALUI SOSIALISASI DAN IMPLEMENTASI SPMI BERDASARKAN PERMENDIKBUDRISTEK NO. 53 TAHUN 2023 - Candra, Dori Gusti Alex; Zaharani Yusno; Leonard Tambunan; Eka Sofiati; Atika Fauziyyah; Budi Permana Putra; Gusra, M. Hafizh; Putra , Khelvin Ovela; Pane, Eddissyah Putra (Mejuajua: Jurnal Pengabdian pada Masyarakat, 2025)
The issuance of Permendikbudristek Number 53 of 2023 marks a paradigm shift in higher education quality assurance from a compliance-based approach to an outcome-based approach. Although it provides greater flexibility and autonomy, this policy also poses challenges in the form of differences in regulatory interpretation, inconsistencies in standards, and the persistent perception that the Internal Quality Assurance System (SPMI) is an administrative burden, especially for universities that are not yet ready to adapt. This community service activity aims to assist the Mitra Gama Institute of Technology (ITMG) in responding to the transition of quality assurance policies in a strategic and applicable manner. The implementation method used a Participatory Action Learning approach, which included an analysis of gaps in SPMI implementation, dissemination of policy perceptions, technical workshops on updating SPMI documents, and internal quality audit simulations to ensure the implementation of the PPEPP cycle. The results of the activity showed a significant increase in participants' understanding of the concept of output-based quality assurance. The percentage of participants who understood the difference between compliance-based and outcome-based approaches increased from 35% before the activity to 90% after the dissemination and workshop. In addition, the perception that the Internal Quality Assurance System (SPMI) was an administrative burden decreased dramatically, from 65% before the activity to 10% after the activity. These findings were reinforced by the increased ability of the quality team to close the PPEPP cycle through the formulation of concrete and measurable corrective actions. Overall, this activity was effective in strengthening the foundation of an adaptive, outcome-oriented internal quality assurance system that supports continuous quality improvement at ITMG.